2020
DOI: 10.14336/ad.2019.0524
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous H2S Promoted USP8 Sulfhydration to Regulate Mitophagy in the Hearts of db/db Mice

Abstract: Hydrogen sulfide (H2S), an important gasotransmitter, regulates cardiovascular functions. Mitochondrial damage induced by the overproduction of reactive oxygen species (ROS) results in myocardial injury with a diabetic state. The purpose of this study was to investigate the effects of exogenous H2S on mitophagy formation in diabetic cardiomyopathy. In this study, we found that exogenous H2S could improve cardiac functions, reduce mitochondrial fragments and ROS levels, enhance mitochondrial respiration chain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…In contrast to DCM in T1DM, cardiac lipotoxicity is a key pathologic mechanism in DCM in T2DM. Some previous studies have shown that cardiac autophagy and mitophagy is inhibited in high-fat diet (HFD)-fed mice (Sciarretta et al, 2012;Guo et al, 2013;Mu et al, 2020;Sun et al, 2020;Yu et al, 2021), but others have shown the opposite. Mellor et al (2011) and Tang et al (2015) found that cardiac autophagy and mitophagy are activated in the hearts of mice and rats with T2DM, respectively, which they stated would be harmful.…”
Section: Mitophagy In Diabetic Cardiomyopathymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to DCM in T1DM, cardiac lipotoxicity is a key pathologic mechanism in DCM in T2DM. Some previous studies have shown that cardiac autophagy and mitophagy is inhibited in high-fat diet (HFD)-fed mice (Sciarretta et al, 2012;Guo et al, 2013;Mu et al, 2020;Sun et al, 2020;Yu et al, 2021), but others have shown the opposite. Mellor et al (2011) and Tang et al (2015) found that cardiac autophagy and mitophagy are activated in the hearts of mice and rats with T2DM, respectively, which they stated would be harmful.…”
Section: Mitophagy In Diabetic Cardiomyopathymentioning
confidence: 99%
“…In the hearts of mice with T1DM, Xu et al (2013) found that the expression of parkin and PINK1 was lower, which implies that mitophagy is impaired in diabetes. Hydrogen sulfide promotes mitophagy in the diabetic heart by increasing the S-sulfhydration of USP8, which increases the deubiquitination of parkin ( Sun et al, 2020 ). Sirt3 overexpression activates mitophagy to reduce myocardial apoptosis in vitro .…”
Section: Mitophagy In Diabetic Cardiomyopathymentioning
confidence: 99%
“…H 2 S has been shown to regulate all significant aspects of mitochondrial dynamics: mitochondrial fusion, mitochondrial fission, mitochondrial macroautophagy/mitophagy, and mitochondrial biogenesis) [ 87 , 94 , 95 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ]. The majority of the published studies indicate that H 2 S (especially in lower concentrations) tends to stabilize and preserve mitochondria, and, in many cases, can also stimulate mitochondrial biogenesis.…”
Section: H 2 S a Regulator Of Mitochondrial Dymentioning
confidence: 99%
“…In the diabetic heart, ubiquitin specific peptidase 8 (USP8) has been implicated: H 2 S was found to increase the association of parkin with USP8. In turn, USP8 (a deubiquitination enzyme) was shown to promote the association of parkin to damaged mitochondria to augment mitophagy [ 145 ]. In another study focusing on cardiac myocytes, H 2 S-stimulated mitochondrial biogenesis was shown to involve AMP-activated protein kinase (AMPK) activation and subsequent induction of PGC1α signaling [ 87 ].…”
Section: H 2 S a Regulator Of Mitochondrial Dymentioning
confidence: 99%
“…and sulfhydration of parkin diminishes, while the persulfidation of parkin protein promotes the activity of ubiquitin E3 ligase, thereby mediating cell protection. H 2 S may upregulate the expression of deubiquitinating enzymes USP8 to antagonize the degradation of Parkin protein (Sun et al, 2020). This implies that H 2 S donors may be potentially therapeutic (Vandiver et al, 2013).…”
Section: Neuroprotective Effects Of H 2 S In Parkinson's Diseasementioning
confidence: 99%